(untitled) (Jurnal Adhyasta Pemilu, 2022)
The abuse of children in the holding of general elections is a form of violation at the campaign stage. Involving children or citizens who do not have the right to vote in political campaign activities is not the right action because children have the right to be free from abuse of political activities. This writing aims to analyze the forms and offer the concept of diversion as protection against child abuse in the General Election. The research method in this writing uses the type of research normative-empirical. The research approach used is a statutory approach and a conceptual approach. The procedure for collecting legal materials uses a literature study, as well as the analysis techniques for legal materials in this study using the descriptive qualitative. The results obtained that the concept of diversion in handling election crimes in which the perpetrators and victims are children can be applied in handling general election violations by the Center of Integrated Law Enforcement Bawaslu, this indicates the importance of further regulation by reformulation and harmonization in the laws and regulations concerning General Elections and it takes effort development of a pattern of repressive and preventive prevention and enforcement strategies in order to provide child-friendly legal protection.